EVALUASI KEBIJAKAN RETRIBUSI PELAYANAN PASAR TRADISIONAL DI KABUPATEN MINAHASA (STUDI DI PASAR TRADISIONAL TONDANO BARAT) - DATUMOLA, ALMA AURELIA; DENGO, SALMIN; KOLONDAM, HELLY (Sam Ratulangi University, 2020)
Public policy evaluation is the activity of assessing the success or failure of a policy whethera policy has had an impact and has achieved the objectives set. Levies are regional levies as payments forcertain services or permits that are specifically provided and / or given by local governments for the benefitof individuals or entities. A traditional market is an open place where buying and selling transactions aremade possible by the bargaining process. In traditional markets visitors are not always buyers, but visitorscan become sellers, and even everyone can sell their wares in traditional markets. In this study using atype of qualitative research in which this research is descriptive in nature that is conducting in-depthinterviews collecting primary data and collecting secondary data, which then results of primary andsecondary data are processed and data will be obtained. The results showed that the achievement ofmarket service levies in the West Tondano Market Has Been Achieved Every Year, It's just that there areseveral monthly targets, namely in certain months there are many red dates so that the achievement ofretribution results cannot be maximized. But overall the results or target levies can already be achieved .Efforts made to achieve retribution include announcing the importance of levy payments. With theachievement of the results of the levy can solve problems that exist in the market such as renovation andprovision of appropriate facilities for market traders. With the costs of levies can be leveled to markettraders in the form of market improvements towards even better. In addition, the existence of levies can beuseful and provide satisfaction for market traders because it can be given appropriate facilities for traders.Keywords: Policy Evaluation, Retribution, Traditional Markets